Topiramate: A Novel Therapeutic Candidate for Diabetes and Aggression? Positron Emission Tomography (PET) Findings - Yulug, Burak; Hanoglu, Lütfü; Mithat Tavli, Ahmet; Cakir, Tansel; Olmuscelik, Oktay; Pakoz, Burak; æ#156;nlü, GülŦ#159;en (Central Nervous System Agents in Medicinal Chemistry, 2016)
Background: There is still limited knowledge regarding the role of impaired brain glucose metabolism in the generation of aggression during diabetes. Additionally, there are rapidly replicating piece of evidence suggesting that topiramate may exert significant mood stabilizing effect. In this respect, we aimed to evaluate the neurometabolic correlates of the therapeutic effect of topiramate in a patient with diabetes and Intermittent explosive disorder (IED). Methods: We measured regional cerebral glucose metabolism using 2-[18F]-fluoro-2-deoxy-D-glucose and positron emission tomography (FDG-PET) in a diabetic patient with aggressive outbursts before and after treatment with topiramate. In order to reveal a defined information underlying the improvement of the aggressive symptoms we also combined the PET with Modified Overt Aggression Scale. Results: We have found that topiramate leads to the improvement in Modified Overt Aggression Scale that was well correlated with the increase in cortical brain metabolism. Discussion: The therapeutic role of topiramate may not only suggest secondary deficits due to diminished functions of the cortical part of emotional circuits but also indicate that diabetic individuals may be vulnerable to lower cerebral glucose metabolism in cortical regions. Further clinical trials that include well-conducted randomized controlled trials and cohort studies by using other methods (i.e., magnetic resonance spectroscopy and quantitative EEG analysis) are necessary to confirm our preliminary findings.
Keywords: Intermittent explosive disorder